Influence of the postplasma process conditions on the surface conductivity of hydrogenated diamond surfaces - Snidero, E; Tromson, D; Mer, C; Bergonzo, P; Foord, J; Nebel, C; Williams, O; Jackman, R (2003)
The influence of the postplasma process on the surface conductivity of hydrogenated diamond surfaces was presented. The influence of dry gases on the hydrogenated diamond surface was also presented. It was found that the hydrogenated surfaces are strongly influenced by the combination of wet air exposure and ultraviolet (UV) light.